Comparative efficacy of different drugs in acute heart failure with renal dysfunction: a systematic review and network meta-analysis - Lv, Qianyu; Wu, Qian; Yang, Yingtian; Li, Lanlan; Ye, Xuejiao; Wang, Shihan; Lv, Yanfei; Wang, Manshi; Li, Yushan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis network meta-analysis was to compare the efficacy of different drugs on cardiac function, renal function, and clinical outcomes in patients with acute heart failure (AHF) accompanied by renal dysfunction.MethodsPubMed, EMBASE, Cochrane Library, and Web of Science were searched to screen all clinical trials of AHF between January 1st 2001 and March 31th 2024. The primary outcome measures were N-terminal pro-B type natriuretic peptide (NT-proBNP), B-type natriuretic peptide (BNP), glomerular filtration rate (GFR), blood urea nitrogen, serum creatinine, all-cause mortality within 60 days, and cardiovascular mortality.ResultsAfter screening 30,697 citations, 13 studies (21,745 patients) were included, and drugs including nesiritide, dopamine, tolvaptan, levosimendan, dobutamine, furosemide, and spirolactone, and high dose of diuretics (HDD, furosemide, and spirolactone) were estimated. The results indicated that HDD had the best efficacy in reducing NT-proBNP levels. In detail, HDD notably reduced NT-proBNP levels compared to conventional treatment or placebo (PLC) [MD = −950.24; 95% CrI (−1,832.21, −64.12)]. Levosimendan significantly increased GFR levels compared to PLC [MD = 14.46; 95% CrI (3.88, 25.97)] and tolvaptan [MD = 13.83; 95% CrI (2.31, 25.33)]. No significant difference was found in 60-day all-cause mortality and cardiovascular mortality across drugs.ConclusionHDD showed the best efficacy in reducing NT-proBNP levels compared with dopamine and nesiritide, and levosimendan could significantly improve GFR levels, with no marked difference in the effect of various drugs on 60-day all-cause mortality. Hence, HDD and levosimendan may be optimal agents in the treatment of AHF with renal dysfunction.Systematic Review RegistrationPROSPERO, identifier (CRD42023454616).